Preparation method of novel AG (anti-glare) glass
The novel anti-glare glass preparation method using MASK technology and photolithography addresses the irregularities of traditional etching by ensuring uniform microstructures, improving anti-glare performance and mechanical strength.
Patent Information
- Application Number
- CN202411484853.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional anti-glare glass preparation methods using frosting etching processes result in irregular and uneven groove structures, affecting anti-glare performance, display effects, mechanical strength, and durability due to uncontrollable chemical reactions.
A novel method involving surface treatment, functional coating, high-precision MASK graphic design, and photolithography to form uniform and consistent microstructures on the glass surface, ensuring precise control over groove shape, size, and distribution.
The method achieves high uniformity and consistency of groove morphology, enhancing anti-glare effect, display quality, and mechanical strength while maintaining high light transmittance and stability across batches.
Smart Images

Figure CN119143400A_ABST
Abstract
Description
Technical Field
[0001] The invention mainly relates to the technical field of glass, and in particular to a method for preparing a novel AG anti-glare glass. Background Art
[0002] Anti-glare (AG) glass is a special glass material widely used in various display devices. Its main function is to reduce reflected light through surface treatment and improve the readability and visual comfort of the screen. In modern society, with the popularization of electronic devices and the continuous improvement of people's requirements for display effects, the demand and technical requirements for AG glass are also increasing. Traditional anti-glare glass is mainly surface treated by frosting etching process. This process is low in cost and simple to operate, but it has many limitations in uniformity, precision and performance. The traditional frosting etching process usually uses a frosting solution containing hydrofluoric acid to chemically treat the glass surface, and forms tiny pit structures on the glass surface through corrosion. These pit structures can scatter reflected light and reduce glare. However, since the chemical etching process is affected by multiple factors such as acid concentration, temperature, reaction time, etc., the final pit structure is often irregular and uneven. This unevenness not only affects the anti-glare performance of the glass, but may also lead to poor display effects and even affect the mechanical strength and durability of the glass. On this basis, a new method for preparing AG anti-glare glass is proposed. Summary of the invention
[0003] 1. Technical problems to be solved by the invention: The present invention provides a novel method for preparing AG anti-glare glass, which is used to solve the technical problems existing in the above-mentioned background technology.
[0004] 2. Technical solution: In order to achieve the above object, the technical solution of the present invention is as follows: A novel method for preparing AG anti-glare glass comprises the following steps: Step 1: Surface treatment of the glass substrate to improve surface adhesion and uniformity; Step 2, uniformly coating a layer of functional coating on the surface of the glass substrate; Step 3, evenly coating the photoresist on the surface of the functional coating, and performing a soft baking treatment after coating; Step 4: Use a high-precision MASK for graphic design and exposure, and accurately transfer the designed microstructure pattern to the photoresist layer so that the graphic size is above 1μm; Step 5: After exposure, developing is performed to remove the unexposed photoresist portion, thereby forming a predetermined pattern on the glass substrate; Step 6: Curing the developed photoresist pattern to ensure that it has sufficient corrosion resistance and stability in the subsequent etching process; Step 7: performing etching to remove unprotected functional coatings and glass substrates to form precise microstructure patterns; Step 8: using photoresist removal technology to remove the remaining photoresist to obtain the final microstructure pattern; Step 9: Functionalize the surface of the microstructure pattern through fluorination treatment to make it have anti-glare and anti-fouling properties.
[0005] A further improvement is that the specific step of step 1 is to perform brush washing, plasma treatment or sol-gel coating on the glass substrate, the treatment temperature range is 20 to 100° C., and the treatment time is 1 to 10 minutes.
[0006] A further improvement is that in step 2, the functional coating is made of silicate, and the thickness of the functional coating ranges from 0.01 to 30 μm.
[0007] Further improvements are: in step 3, the thickness of the photoresist ranges from 0.01 to 30 μm, the soft baking temperature ranges from 50 to 250° C., and the soft baking time ranges from 1 to 10 minutes.
[0008] A further improvement is that the MASK graphic design in step 4 is formed by splicing multiple small-sized drawings, and high-precision graphic transfer is achieved through this splicing design.
[0009] A further improvement is that the developing time in step 5 is 1 to 10 minutes.
[0010] A further improvement is that in step 6, the curing is performed by heat curing or UV curing, the temperature range is 50 to 500° C., and the curing time is 1 to 60 minutes.
[0011] A further improvement is that in step 7, the etching solution uses a single acid or mixed acid containing fluoride ions, and the depth of the etching pattern is controlled between 0.5 and 50 μm.
[0012] A further improvement is that the method of removing the photoresist in step 8 is wet removal or dry removal, and the removal time is 1 to 15 minutes.
[0013] A further improvement is that the temperature range of the fluorination treatment in step 9 is 20 to 100° C. and the treatment time is 1 to 60 minutes.
[0014] 3. Beneficial effects: Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: The present invention realizes high-precision pattern transfer through MASK technology, and uses photolithography to accurately transfer the designed microstructure pattern to the glass surface to form a highly consistent groove morphology. The shape and size of the groove can be accurately controlled through MASK design, thereby ensuring the relative uniformity and consistency of the surface structure. Compared with the traditional frosting etching process, MASK technology can effectively avoid the problem of inconsistent groove shape and size, and ensure the stability of the anti-glare effect; By adjusting the MASK design, the present invention can accurately set the number and density of grooves within a specific area and optimize the area ratio of the pattern, so that the present invention can flexibly adjust the glass surface structure to achieve the best anti-glare effect; The MASK technology used in the present invention ensures the relative consistency of the grooves in shape, size and depth, significantly improves the uniformity of the glass surface, makes the light scattering effect more uniform, significantly improves the display effect, and solves the problem of disordered groove distribution in traditional processes; The process stability and controllability of the present invention are enhanced, ensuring the consistent quality of each batch of products, while maintaining high light transmittance and mechanical strength, thereby improving the display effect and durability of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A flow chart of the preparation method of the novel AG anti-glare glass provided by the present invention; Figure 2 The morphology and cross-sectional view of the frosted AG glass and the AG glass after yellow light MASK graphic design provided by the present invention; Figure 3 This is a comparison diagram of the graphic design of the conventional frosted AG glass of the present invention and the AG glass after the yellow light MASK graphic design; Figure 4 The anti-glare phenomenon of the traditional masked AG glass and the AG glass with yellow MASK graphic design under light in the present invention; Figure 5 It is the average chromaticity of the traditional frosted AG glass of the present invention and the AG glass after yellow light MASK graphic design under different conditions. DETAILED DESCRIPTION
[0016] To facilitate understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. Several embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0017] Before introducing the present invention, the following main defects of the conventional frosting etching process in preparing anti-glare glass are introduced in detail: Defect 1: The groove shape and size are inconsistent: The traditional frosting etching process forms a groove structure on the glass surface through chemical reaction, but due to the uneven diffusion and reaction of the acid, the shape and size of the grooves formed are inconsistent, and the surface morphology shows obvious randomness. This inconsistency directly affects the anti-glare performance of the glass, making it impossible to evenly scatter the reflected light, resulting in poor display effects.
[0018] Defect 2: disordered groove distribution: Due to the uncontrollability of the etching process, the distribution of the grooves is disordered and cannot form a regular or orderly pattern. The disordered distribution of grooves not only reduces the anti-glare effect, but may also form local light spots or dark spots on the glass surface, affecting the visual experience.
[0019] Defect 3: Large difference in groove depth: The depth of the grooves formed by the traditional frosting etching process varies greatly, with different depths and a wide range of depths. The groove structure with large depth differences will produce different scattering effects when reflecting light, resulting in uneven surface light scattering and unable to achieve the ideal anti-glare effect.
[0020] Defect 4: Large surface roughness: The microstructure formed on the glass surface by the frosting etching process has a large roughness, which not only affects the light scattering effect, but also may reduce the light transmittance of the glass and affect the display effect. In addition, glass with a large surface roughness is more likely to accumulate dust and dirt during use, making it more difficult to clean.
[0021] Defect 5: Poor process stability: Since the chemical etching process is affected by many factors, the stability of the traditional frosting etching process is poor, and it is difficult to ensure the consistency of each batch of products. This poses a challenge to large-scale production and application, and increases the difficulty of quality control.
[0022] On this basis, specific reference Figure 1 The present invention proposes a novel AG anti-glare glass preparation method, comprising the following steps: glass substrate surface treatment → functional coating deposition → patterned photoresist coating → MASK pattern design and exposure → development → photoresist pattern curing → etching → photoresist removal → post-processing.
[0023] Specifically, the surface treatment of the glass substrate includes the following steps: First, the glass substrate is brush washed, plasma treated or sol-gel coated to improve surface adhesion and uniformity. The treatment temperature range is 20-100°C and the treatment time is 1-10 minutes. This step ensures the stability of the subsequent coating and etching process.
[0024] Specifically, the functional coating deposition includes the following steps: A layer of functional material (such as silicate or polymer) is coated on the surface of the glass substrate by spin coating, dip coating, spray coating, or coating. The thickness of the coating ranges from 0.01 to 30 μm to ensure uniform coverage and meet the required process requirements. The functional coating is used to improve the optical properties and etching uniformity of the surface.
[0025] Specifically, the patterned photoresist coating includes the following steps: The photoresist is coated on the surface of the functional coating, and the coating is evenly applied by spin coating or spray coating. The thickness of the photoresist ranges from 0.01 to 30 μm to ensure uniform coverage and meet the required process requirements. After coating, soft baking is performed at a temperature range of 50 to 250°C and a soft baking time of 1 to 10 minutes.
[0026] Specifically, MASK graphic design and exposure includes the following steps: After patterned photoresist is applied on the functional coating, high-precision MASK is used for graphic design and exposure. This step uses a proximity or projection exposure machine to accurately transfer the designed microstructure pattern to the photoresist layer through MASK technology. By adjusting the parameters, the size, uniformity, arrangement and morphology of the microstructure can be controlled to ensure that the graphic size is above 1μm. MASK graphic design can accurately control the shape and size of each groove so that it is evenly distributed on the entire glass surface. Using high-precision MASK, complex pattern designs can also be achieved, such as different microstructure layouts such as honeycomb and array, thereby optimizing anti-glare effects and light scattering performance.
[0027] Specifically, the development includes the following steps: After exposure, development treatment is carried out. The type and concentration of the developer are selected according to industrial standards. The development time is 1 to 10 minutes. The purpose of the development step is to remove the unexposed photoresist portion, thereby forming a predetermined pattern on the glass substrate. The developed pattern should have good edge clarity and dimensional accuracy to meet the requirements of the subsequent etching process.
[0028] Specifically, the photoresist pattern curing includes the following steps: The developed photoresist pattern needs to be further cured to ensure that it has sufficient corrosion resistance and stability in the subsequent etching process. The curing can be carried out by thermal curing or UV curing. The temperature range is 50-500°C and the curing time is 1-60 minutes. The curing parameters are adjusted according to the type of photoresist to achieve the best curing effect.
[0029] Specifically, etching includes the following steps: Etching treatment is carried out, and the etching solution uses a single acid or mixed acid containing fluoride ions. The acid type can be selected as bubble type, top spray type or horizontal type. The depth of the etching pattern is controlled between 0.5 and 50μm. The purpose of etching is to form a precise microstructure pattern by removing unprotected functional coatings and glass substrates. The etching process parameters are designed according to the specific graphics to ensure the high precision and high quality of the final product.
[0030] Specifically, the photoresist removal process includes the following steps: Use photoresist removal technology to remove residual photoresist and obtain the final microstructure pattern. The photoresist can be removed by wet removal or dry removal, and the removal time is 1 to 15 minutes. This step ensures that there is no residual material on the surface to prepare for subsequent processing.
[0031] Specifically, post-processing includes the following steps: The microstructure surface is functionalized through fluorination or other chemical modification methods to make it have anti-glare and anti-fouling properties. The temperature range of fluorination treatment is 20-100°C and the treatment time is 1-60 minutes. Surface functionalization treatment can further enhance the optical properties and durability of the glass, ensuring its excellent performance in practical applications.
[0032] The manufacturing process provided by the present invention combines photolithography technology and MASK design. By precisely controlling the shape, size and distribution of the pits, a relatively uniform and regular microstructure is formed on the glass surface. This microstructure not only significantly improves the anti-glare effect, but also maintains the high light transmittance and mechanical strength of the glass. It is a major advancement in the anti-glare glass preparation technology.
[0033] The yellow light AG glass prepared by the above preparation method is compared with the traditional frosted AG glass, and several traditional frosted AG glasses compared below are prepared under the same conditions, and the compared yellow light AG glasses are also prepared under the same conditions. It should be noted that although the above preparation method gives an applicable scope, the products corresponding to different scopes are structurally consistent, and what is changed is the aperture size, including depth and width. Therefore, the yellow light AG glass prepared by the above preparation method is used for experimental verification.
[0034] The preparation process of traditional frosted AG glass includes the following steps. First, the glass is thoroughly cleaned to remove dust and oil on the surface. Then, frosting is performed by chemical or physical methods, and the glass surface is corroded by acidic or alkaline solutions, or the surface is physically ground using sandblasting technology to form a uniform rough layer. Subsequently, an anti-reflective coating is applied to the frosted glass to reduce the light reflectivity and enhance the anti-glare effect. Some glass is also heat-treated to increase its strength. Finally, the finished product is strictly quality-tested to ensure that its optical properties and physical strength meet the requirements, and then it is packaged and shipped after cleaning. Since the preparation process of traditional frosted AG glass belongs to the prior art, it will not be described in detail here.
[0035] Please refer to the attached Figure 2 , shown are the morphology and cross-section of traditional frosted AG glass (Figures A&C) and AG glass after yellow light MASK graphic design (Figures B&D).
[0036] Figure 2 Figures A and C in the middle show that the surface morphology of AG glass prepared by the traditional frosted etching process has significant defects. As can be seen from the image, this process leads to irregular arrangement of grooves on the glass surface. The diameter of the grooves ranges from 10 to 50 μm, and the shapes and sizes are inconsistent, showing obvious randomness. The distribution of the grooves is disordered and cannot form a regular or orderly pattern. Due to the different sizes of the patterns, the depths of the patterns under the same etching conditions are different (0.3-3UM), which affects the uniformity of the surface and causes uneven light scattering, thus affecting the anti-glare effect and visual experience.
[0037] At the same time, Figures A and C show that the cross-section shape is irregular, the edges are blurred, and the transition area is wide. These characteristics indicate that the traditional etching process has great deficiencies in controlling the depth and shape of the grooves, resulting in an uneven surface and an uneven overall structure. This irregular and uneven groove morphology directly affects the scattering characteristics of light and cannot achieve the ideal anti-glare effect.
[0038] In contrast, the AG glass surface after MASK graphic design has higher precision and consistency, such as Figure 2 In Figures B and D, the grooves are highly consistent in shape and size, with a particle size range of 20 to 40 μm, evenly distributed, forming a regular honeycomb pattern. The grooves are arranged in an orderly manner, which can accurately control the arrangement and morphology of the pattern, and the size is relatively consistent, so that under the same etching conditions, the depth changes little and is basically consistent, ranging from 0.5 to 1.5 μm, thereby improving the uniformity of the surface. The product is specifically characterized by uniform roughness. The roughness corresponding to Haze 20%\30%\40% is Haze20% corresponding Ra: 0.32±0.1um; Haze30% corresponding to Ra: 0.4±0.15um; Haze40% corresponds to Ra: 0.45±0.15um.
[0039] The roughness ranges of the AG glass and frosted glass prepared by this method are obviously different.
[0040] As attached Figure 3 As shown, the MASK pattern used in the present invention is designed through splicing. The specific method is to use multiple small-sized drawings, including 1x1mm, 2x2mm, 3x3mm...NxNmm, etc. to splice together. High-precision pattern transfer is achieved through this splicing design. The key to this method lies in precise drawing design and splicing process, so that the final mask can generate a uniform and regular microstructure on the glass surface.
[0041] pass Figure 3 In A and B, the effect of the splicing design can be intuitively seen. Picture A shows the AG glass after the splicing mask treatment, and its surface has a matrix pattern and certain splicing marks. The splicing marks are visible under an illumination greater than 1500LUX, which is a significant feature of the present invention. Picture B is the corresponding splicing drawing design, showing the precise design of each small unit and the overall effect after splicing. In contrast, pictures C and D show the traditional frosted AG glass and its corresponding drawing design, and its surface has no significant regular microstructure and matrix features.
[0042] The spliced MASK greatly reduces the computer memory usage and software running time, and improves the overall work efficiency. Whether it is spliced in squares of any size, or in rectangles or triangles, or in other symmetrical or mirrored patterns, it is within the protection scope of the present invention.
[0043] As attached Figure 4 As shown in the figure, the anti-glare phenomenon of different types of AG glass under light is shown. A, B, and C respectively represent the performance of AG glass with MASK graphic design under light, and their hazes are 40, 30, and 20 respectively. D, E, and F show the performance of frosted AG glass prepared by traditional technology under the same conditions (i.e., hazes of 40, 30, and 20). By comparison, it can be seen that with the decrease of haze, the anti-glare effect of both types of AG glass changes.
[0044] The pattern of the AG produced by the present invention under strong light illumination is obviously different from that of the traditional frosting, which is also an important feature of the present invention. The frosting is in a three-layer circle shape, and the reflection intensity of light becomes lower and lower from the inside to the outside. The present invention adopts a MASK pattern design, which is also in a 2-3 circle shape, but the strong contrast is not obvious, but in a rainbow shape, indicating that the AG product of the present invention has a better light scattering effect, which is one of the important features of the present invention.
[0045] As attached Figure 5 The average chromaticity of the two glasses under different conditions is shown.
[0046] By testing and comparing the chromaticity values of the frosted AG glass produced by the traditional process and the AG glass produced after the yellow light MASK graphic design, it is found that the yellow light AG glass shows certain differences in brightness value (L*), red-green value (a*) and yellow-blue value (b*). The brightness value of the AG glass of the present invention is lower, the surface is darker, the red-green value shows a slight red hue, and the yellow-blue value shows a yellow hue. The frosted AG glass has a higher brightness value, a brighter surface, a slight green hue in the red-green value, and a blue hue in the yellow-blue value.
[0047] The test results of adding LCM screen and black screen state show that the brightness value, red-green value and yellow-blue value of AG glass and frosted AG glass of the present invention before and after adding screen all show significant changes. After adding black screen, the brightness value is significantly reduced, which is similar to the difference of single body; The above data show that the AG glass of the present invention exhibits more excellent properties in chromaticity value and has a lower brightness value. Specifically, when the a* and b* values of the glass are both within the range of ±1, the L value of the AG glass monomer of the present invention is <33, and the L value in the black screen state after being bonded to the LCM screen is <28, and the L value is significantly lower than that of frosted glass by about 1-2 points.
[0048] The above-described embodiments only express a certain implementation mode of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A novel method for preparing AG anti-glare glass, characterized in that: The following steps are involved: Step 1: Surface treatment of the glass substrate to improve surface adhesion and uniformity; Step 2, uniformly coating a layer of functional coating on the surface of the glass substrate; Step 3, evenly coating the photoresist on the surface of the functional coating, and performing a soft baking treatment after coating; Step 4: Use a high-precision MASK for graphic design and exposure, and accurately transfer the designed microstructure pattern to the photoresist layer so that the graphic size is above 1μm; Step 5: After exposure, developing treatment is performed to remove the unexposed photoresist portion, thereby forming a predetermined pattern on the glass substrate; Step 6: Curing the developed photoresist pattern to ensure that it has sufficient corrosion resistance and stability in the subsequent etching process; Step 7: performing etching to remove unprotected functional coatings and glass substrates to form precise microstructure patterns; Step 8: using photoresist removal technology to remove the remaining photoresist to obtain the final microstructure pattern; Step 9: Functionalize the surface of the microstructure pattern through fluorination treatment to make it have anti-glare and anti-fouling properties.
2. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: The specific steps of step 1 are brush washing, plasma treatment or sol-gel coating of the glass substrate, the treatment temperature range is 20 to 100° C., and the treatment time is 1 to 10 minutes.
3. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 2, the functional coating is made of silicate, and the thickness of the functional coating ranges from 0.01 to 30 μm.
4. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 3, the thickness of the photoresist ranges from 0.01 to 30 μm, the soft baking temperature ranges from 50 to 250° C., and the soft baking time ranges from 1 to 10 minutes.
5. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 4, the MASK graphic design is made by splicing multiple small-sized drawings, and high-precision graphic transfer is achieved through this splicing design.
6. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: The developing time in step 5 is 1 to 10 minutes.
7. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 6, the curing is performed by heat curing or UV curing, the temperature range is 50 to 500° C., and the curing time is 1 to 60 minutes.
8. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 7, the etching solution uses a single acid or mixed acid containing fluoride ions, and the depth of the etching pattern is controlled between 0.5 and 50 μm.
9. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: In step 8, the photoresist is removed by wet removal or dry removal, and the removal time is 1 to 15 minutes.
10. The method for preparing a novel AG anti-glare glass according to claim 1, characterized in that: The temperature range of the fluorination treatment in step 9 is 20 to 100° C., and the treatment time is 1 to 60 minutes.
Citation Information
Patent Citations
Manufacturing method of anti-dazzling cover plate and display device
CN107217262A
Anti-dazzle glass processing method and product thereof
CN116573863A
Cited By
Method for integrating texture pattern and anti-glare pattern and glass substrate
CN120004516A
Preparation method of anti-glare glass
CN120208552A
A method for preparing anti-glare glass
CN120208552B
Microcrystal texture glass cover plate and preparation method thereof
CN120590066A
Anti-glare glass and preparation method thereof
CN120943537A
